Analisis Tipe Fasies Hidrokimia Air tanah Berdasarkan Kondisi Litologi di Desa Olele, Kecamatan KabilaBone, Kabupaten Bonebolango - Pratiansyah Karim; Nurfaika Nurfaika; Ahmad Zainuri (-, 2026)
This research was conducted in Olele Village, Kabila Bone District, Bone Bolango Regency, Gorontalo Province. The study aims to analyze the relationship between lithology and groundwater hydrochemistry and to determine the groundwater hydrochemical facies. The methods used include surface geological mapping, groundwater chemical analysis at the Chemistry Laboratory of Universitas Negeri Gorontalo, and determination of hydrochemical facies using the Piper trilinear diagram. The results of groundwater chemical analysis plotted on the Piper diagram indicate that the hydrochemical facies in the study area is dominated by the Na–Cl facies. This facies suggests the influence of seawater mixing or seawater intrusion into the coastal aquifer system. This condition is reinforced by reef limestone lithology, which has high porosity and permeability, allowing seawater to enter the shallow groundwater aquifer. Thus, reef limestone lithology plays an important role in controlling the aquifer system and influencing groundwater hydrochemical characteristics. Interaction between groundwater and the coastal environment causes groundwater to evolve toward the Na–Cl facies.